Construction of intelligent campus tennis players' body data monitoring and injury warning system based on data fusion - Li, Y. (Revista Brasileira de Medicina do Esporte, 2021)
As far as competitive sports are concerned, scientifically organizing the training process and strictly following the training rules are the only way to success. Tennis is the foundation of all sports. It develops physical and motor skills in a comprehensive and effective manner. Biomechanical diagnosis is mainly carried out on the basis of force-time curve recording of different movement modes, and the generated data is processed by computer through a special measuring device. The main purpose of this study is to use data fusion technology to analyze and evaluate the injury factors involved in various sports. Based on this, a dynamic chain model for early warning of sports injury risk factors is established, which can provide a reference for athletes to avoid and reduce the risk of injuries and ensure normal training and competition. In tennis training, scientific training monitoring is applied to diagnose and monitor athletes` physical function and psychological state. Conduct humanized and scientific management of the training process.